Innovation and sustainability in Anambra State Civil Service, Nigeria - Emeka, Omaliko; Kelvin, Mordi; George, Ezeala (International Journal of Financial, Accounting, and Management, 2025)
Purpose: This study empirically investigated the relationship between innovation and sustainability in the Anambra State Civil Service. Method: Three hypotheses were formulated to guide the investigation, and hypothesis testing was conducted using the least-squares regression model. Hence, data were collected using an e-questionnaire survey sent to the respondents (staff of the Ministry of Finance and Ministry of Budget and Economic Planning) through their various WhatsApp group platforms, out of which 112 responses were recorded, received, and used in the data analysis. Results: A positive and significant influence was found between innovation and sustainability in the Anambra State Civil Service at the 1% significance level. The study therefore concludes that the advent of technological innovation, administrative innovation, and organizational innovation have led to sustainability in the Anambra State Civil Service. Thus, innovation determines sustainability in the Anambra State Civil Service. In lieu of this, the study recommends that civil servants be encouraged to be innovative by appropriately rewarding every innovative idea. Conclusions: The study concludes that the advent of technological innovation, administrative innovation, and organizational innovation have led to sustainability in the Anambra State Civil Service. Limitations: Some of the respondents did not attend the e-questionnaire. Thus, notwithstanding, a thorough work was carried out.   Contribution: This study contributed to knowledge by designing a model variable and updating the literature on the subject. Novelty: This study introduces a new idea on innovation obtainable in the Anambra State Civil Service.